Wearable Pressure Sensors: Facile Fabrication of Ultraflexible Transparent Electrodes Using Embedded Copper Networks for Wearable Pressure Sensors (Adv. Mater. Technol. 2/2020). Issue 2 (10th February 2020) - Li, Peng; Zhao, Yang; Ma, Jiangang; Yang, Yang; Xu, Haiyang; Liu, Yichun
Abstract : In article number 1900823, Jiangang Ma and co‐workers design a wearable pressure sensor based on an embedded copper network which is capable of detecting low pressure of 1.1 Pa with high sensitivity of 76.1 kPa −1, surpassing the subtle pressure sensing properties of natural skin. Such transparent and simple pressure sensors have potential for use as electronic skins and human–machine interfaces to monitor heat rate and breathing.